Hypercapitalism and Product Commodification through Digital-based Marketing Communications in Komodo National Park - Lusia Vreyda Adveni; Geofakta Razali (International Journal of Travel, Hospitality and Events, 2022)
ABSTRACT Purpose: This research aims to analyze the value of hypercapitalism and product commodification through marketing communication strategies in one of Indonesia's flagship eco-tourism named Komodo National Park. Research methods: The approach used in this study is to review the literature review and conduct in-depth interviews with tourism players in Komodo National Park (KNP). Results and discussion: The results showed that KNP eco-tourism is still ongoing as the renewal and development of information technology affect digital marketing in the tourism sector. Implication: It is hoped that all parties and stakeholders involved in KNP eco-tourism can assume that the main motivation for development is not only profit by sacrificing marine ecosystems and destroying existing habitats. Keywords: hypercapitalism, commodification, digital marketing, eco-tourism, Komodo National Park.